Application of chia (Salvia hispanica) mucilage as an ingredient replacer in foods. (September 2021) - Chiang, Jie Hong; Ong, Dayna Shu Min; Ng, Felicia Siew Kay; Hua, Xin Yi; Tay, Wesley Li Wen; Henry, Christiani Jeyakumar
Abstract: Background: Polysaccharides derived from plant seeds such as Chia ( Salvia hispanica ) have garnered significant interest within the food industry in recent years due to their unique functional properties. Known as chia mucilage (CM), it is a functional ingredient with a high amount of dietary fibre and macro- and micro-nutrients. CM also contains an abundance of health-promoting oligosaccharides that can be incorporated into foods for good gut health. Scope and approach: This review aims to provide an overview of the isolation process of CM regarding the parameters used and yields obtained. Examples of parameters adapted in the extraction of CM include hydration conditions (temperature, time, water/seed ratio and pH), extraction and purification methods, and recovery parameters. Applications of CM as ingredient replacers, namely fat/oil, egg, gluten, emulsifier/stabiliser, and phosphate replacers, in various foods such as baked, cereal, dairy, and meat products are also discussed. Key findings and conclusions: The effects of the isolation process and processing parameters on the experimental yield and proximate compositions of CM produced are summarised. The application of CM as ingredient replacers is also discussed, which further places importance on understanding the unique functional properties of CM for it to be utilised in other food products. It was concluded that CM is a valuable food ingredient that has been shown to impart functionality in a variety of food products, and the potential of using CM could be increased in the future. Highlights: Different isolation processes of chia mucilage were discussed. Rate of mucilage release is controlled by hydration parameters. Overview of chia mucilage in different food applications. Chia mucilage is used as ingredient replacers in food product development.